Indications and Long-Term Outcomes of Neck Lift Versus Neck Liposuction: A Comparative Study - Kamal Uddin Khan, Farzana Abdullah, Ajwa Tariq Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Neck rejuvenation is a cornerstone of facial aesthetic surgery, addressing issues such as skin laxity, submental fat, and platysmal banding. While neck lift surgery offers structural support and long-term correction, neck liposuction presents a minimally invasive alternative with quicker recovery. There remains limited comparative data on the long-term outcomes and patient satisfaction associated with these two techniques in South Asian populations, particularly in Balochistan and Islamabad. Materials and Methods: A prospective, comparative study was conducted from March 2022 to March 2023 at Bolan Medical Complex (Quetta) and a private surgical center in Islamabad. A total of 80 patients were enrolled—40 underwent neck lift surgery (Group A) and 40 underwent neck liposuction (Group B). Patient selection was based on clinical indication, anatomical evaluation, and patient preference. Standardized tools including the Visual Analog Scale (VAS), FACE-Q, and WHOQOL-BREF were used to assess satisfaction and quality of life at baseline, 3 months, and 12 months postoperatively. Statistical analysis was performed using SPSS 25.0, with one-way ANOVA and Pearson correlation applied. A p-value <0.05 was considered statistically significant. Results: Group A demonstrated significantly higher satisfaction scores at 12 months (VAS: 8.7 ± 0.9) compared to Group B (VAS: 7.1 ± 1.2; p<0.001). FACE-Q satisfaction scales also favored the neck lift group. WHOQOL-BREF revealed notable improvements in psychological and social domains in Group A. One-way ANOVA confirmed statistical significance across all metrics, and a moderate positive correlation (r=0.41; p<0.01) was found between aesthetic satisfaction and QoL improvements. Conclusion: Neck lift surgery yields superior long-term aesthetic outcomes and quality of life improvements compared to neck liposuction. These findings highlight the importance of individualized treatment planning and long-term patient counseling in facial cosmetic surgery. Keywords: Neck lift, Neck liposuction, Aesthetic surgery, Patient satisfaction, FACE-Q, WHOQOL-BREF, Balochistan, Islamabad